The Effect of Time Application from Nasa Liquid Organic Fertilizer on The Generative Phase of Sponge Plants (Luffa acutangula L.) - Ronny Mulyawan; Danu Kurniawan Putra; Tuty Heiriyani (Warmadewa University Press, 2024)
The study was to determine the effect of the time of application from NASA liquid organic fertilizer on the generative phase of sponge plants (gambas). In cultivating plants, there are several obstacles faced such as less fertile soil and fertilization that is not on target, causing production results to be not optimal. One way that can be done to increase crop production is using NASA's POC. This research was carried out at Lahan Percobaan of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The research method used was a study using a one-factor Randomized Group Design (RGD) with 4 treatments and 5 tests so that 20 experimental units with a NASA LOF concentration of 2 ml.l-1 water were obtained. The treatment to be applied is: P0 = without giving NASA LOF, P1 = giving NASA LOF (application at 2 WAP), P2 = giving NASA LOF (application at age 2 and 4 WAP), P3 = giving NASA LOF (application at age 2, 4 and 6 WAP). The results showed that the timing of NASA's LOF It has no effect on the parameters of fruit length, fruit diameter, fruit weight and number of fruits of sponge plants, but has a noticeable effect on the parameters of the number of male flowers and the number of female flowers of sponge plants. NASA's POC application with a time interval of 3 times (P3) showed the best results in the parameters of the number of male flowers as many as (9.32) flower florets and (3.28) florets the number of female flowers.